Fisheries Development Policy In Bengkalis District - Sugara, Robi; Sujianto, Sujianto; Yuliani, Febri (POLITICO, 2023)
ABSTRACT As the world's largest archipelagic nation, Indonesia dominates vast oceans and fishing As the world's largest archipelagic nation, Indonesia dominates vast oceans and fishing grounds (rich in fish). The country is already one of the largest aquaculture producers in the world. However, like other sectors of the economy, the country has not fully exploited the potential of the fishing sector to optimize profits. The purpose of this research is 1. analysis of fisheries development policy in Benkali district, 2. It analyzes the factors influencing fisheries development policies in Benkali district. A qualitative research method was used as the research method. The results of this study are included in the Fisheries Development and Development Policy of Benkali District. This consists of transparency, the need for transparency in the organization, especially in relation to the state budget, and the aquaculture development program cannot be separated from participation. Community participation component of fisheries development policy during Benkali's reign. The factors affecting fisheries development in Benkalis consist of conflicting goals, and the Regency government, especially the Benkalis District Fisheries Department, has attempted to coordinate the goals of fisheries development with the district's fisheries management. Keyword : Politics, Fisheries Development, Benkali District